Investigation of Weld Characteristics of Stainless Steel Material Fabricated by TIG Welding Process: A Review - S., RAMKI; K. , SHANMUGANANTHAM; S. , SURESH KUMAR (International Journal of Psychosocial Rehabilitation, 2020)
The welding process for SS410 metal by using TIG welding voltage, gas flow rate, and strike-off distance were selected to ascertain with effect on the metal hardness of the welding bed. The NDT technique is used to detect the welding bed. SS410 has gathered wide acceptance in the fabrication of light-weight structures requiring a high strength-to-weight ratio and good corrosion resistance. Modern structures concept demand reduction in the weight as the cost of production and fabrication of the material 410 SS joints are inevitable for certain application due to unique performances such as corrosion resistance and mechanical properties the process welding parameters like current voltage gas flow rate of TIG for getting maximum weldment and best mechanical properties the analysis of the test result is conducted using a welding parameter range that, given best result, found this combination can be considered a good range for TIG welding of SS410 material and conduct the study of temperature distribution and total heat flux of welding area using the analysis. The scope of arc welding has to be increased in the various engineering field like aerospace nuclear and under water industries where complex geometry and hazardous environments necessitate fully automated systems. Even traditional application of arc welding, such as off-highway and automotive manufacturing, have to be increased due to their demand in quality cost accuracy and volume to stay competitive As a result, process parameter are needed to improve the existing process weld